The Fossil Hunter - Cooper, Tea ([Nashville] : Harper Muse, 2022)
"From USA TODAY bestselling author Tea Cooper comes the story of how a fossil discovered at London's Natural History Museum leads one woman back in time to nineteenth-century Australia and a world of scientific discovery and buried secrets"--
Keywords: Missing persons -- Fiction; Fossils -- Fiction; Secrecy -- Fiction; Paleontologists -- Fiction; Secrecy -- Fiction; World War I -- Fiction; Australia -- Fiction; FICTION / Mystery & Detective / Historical; FICTION / Romance / Historical / 20th Century; Historical fiction; Detective and mystery fiction